Improving the Quality of Smoked Fish Products to Ensure the Existence of the Polkhastar Group May Blessings Come Through Diversification of Fishery Products in the Digital Age - Ruslan A. Daeng; Umar Tangke; Ali Lating; Putri Fani Batibae; Irgi Amatory Naim; Siti Umra Ube (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
This community service article discusses efforts to improve the quality of smoked fish products among the Polkhastar Semoga Berkah group in Ternate City, North Maluku. The main problems faced are low quality consistency, limited product diversification, and minimal use of digital marketing. Through a participatory approach, the community service activities included training on product quality improvement using GMP and SSOP standards, product diversification development such as smoked fish flakes, smoked fish sambal, and ready-to-eat instant products, as well as digital marketing training through social media and marketplaces. The results of the activities showed an improvement in product quality, diversification that expanded the market, and increased sales through digital platforms. In addition, strengthening the group's institutional capacity through business management training reinforced the sustainability of the business. In conclusion, the integration of quality improvement, diversification, and digital marketing is a holistic strategy to ensure the existence of fish processing groups in the digital era.